2016
DOI: 10.1039/c5tx00421g
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cytotoxicity towards microglia of iron oxide (α-Fe2O3) nanorhombohedra

Abstract: Understanding the nature of interactions between nanomaterials, such as commercially ubiquitous hematite (α-Fe2O3) Nanorhombohedra (N-Rhomb) and biological systems is of critical importance for gaining insight into the practical applicability of nanomaterials. Microglia represent the first line of defense in the central nervous system (CNS) during severe injury or disease such as Parkinson’s and Alzheimer’s disease as illustrative examples. Hence, to analyze the potential cytotoxic effect of nanorhombohedra ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…[29][30][31] In particular, ROS generation could trigger a wide range of transcriptional changes as the second messengers in a signaling cascade, and it might be recovered after leading to apoptosis or cell death. [32][33][34][35][36] In this study, the level of ROS production was detected after treatment of NCI-H460 cells with CDA14 and CDO14 liposomes for 24 h. The results showed that the intracellular ROS level was dose-dependent and increased significantly compared with the control in NCI-H460 cells. The ROS production of CDA14 was higher than that of CDO14 at the same concentrations; in particular, the ROS production of CDA14 increased remarkably at 120 μg Fig.…”
Section: Effects On the Mmpmentioning
confidence: 74%
“…[29][30][31] In particular, ROS generation could trigger a wide range of transcriptional changes as the second messengers in a signaling cascade, and it might be recovered after leading to apoptosis or cell death. [32][33][34][35][36] In this study, the level of ROS production was detected after treatment of NCI-H460 cells with CDA14 and CDO14 liposomes for 24 h. The results showed that the intracellular ROS level was dose-dependent and increased significantly compared with the control in NCI-H460 cells. The ROS production of CDA14 was higher than that of CDO14 at the same concentrations; in particular, the ROS production of CDA14 increased remarkably at 120 μg Fig.…”
Section: Effects On the Mmpmentioning
confidence: 74%
“…Tissue fixation and staining was performed as previously described [28]. Briefly, for evaluation of tumor tissue at different time points, mice were deeply anesthetized with 2.5% avertin i.p.…”
Section: Methodsmentioning
confidence: 99%
“…represents the most stable phase and assumes direct applications in many fields [35][36][37][38]. Hematite can be formed through oxidation of Fe 3 O 4 at room temperature [39 ,40]:…”
Section: Hematite (α-Fe 2 O 3 ) Clustermentioning
confidence: 99%